2019
DOI: 10.1017/jfm.2019.618
|View full text |Cite
|
Sign up to set email alerts
|

Extreme long waves over a varying bathymetry

Abstract: Recent modelling work has shown that abrupt bathymetric transitions can produce dramatic amplifications of long waves, under the influence of both nonlinearity and dispersion. Here, the evolution of wave packets towards a vertical wall over a varying bathymetry is investigated with a one-dimensional conformal-mapping spectral code. In this system, wave breaking, runup and reflection, wave interference and bathymetric effects are highlighted. Wave breaking is examined with respect to geometric, kinematic and en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…These deep‐water values translate to 9–13m SWH at the coast (Janjić, ; Cox et al ., ). Maximum wave heights (for rare individual waves) may have been as much as twice the SWH; and nonlinear interactions with uneven topography near the steep coasts may have generated additional amplifications (Brennan et al ., ; Herterich and Dias, ). The waves were big!…”
Section: Winter 2013–2014: the North Atlantic ‘Storm Factory’ And Itsmentioning
confidence: 98%
See 1 more Smart Citation
“…These deep‐water values translate to 9–13m SWH at the coast (Janjić, ; Cox et al ., ). Maximum wave heights (for rare individual waves) may have been as much as twice the SWH; and nonlinear interactions with uneven topography near the steep coasts may have generated additional amplifications (Brennan et al ., ; Herterich and Dias, ). The waves were big!…”
Section: Winter 2013–2014: the North Atlantic ‘Storm Factory’ And Itsmentioning
confidence: 98%
“…Observations and analysis have shown that nonlinear interactions at steep coasts can induce very large waves—‘rogue’ or ‘freak’ waves, defined as greater than twice the local significant wave height (SWH) (Didenkulova and Pelinovsky, ; Fedele et al ., ). Numerical modelling reveals that irregular bathymetry adjacent to steep coasts may drive further exceptional amplifications (Akrish et al ., ; Brennan et al ., ; Herterich and Dias, ). Finally, the photography explosion of the last decade or so has resulted in a constantly growing trove of stunning images, which is essentially a citizen‐science dataset of the extraordinary run‐up associated with storm waves at steep coasts (Figure ).…”
Section: Recent Discoveries Prove That Storm Waves Can Move Even the mentioning
confidence: 98%
“…The fast velocities, changing crest shape, fluid mixing and rapid development of breaking waves over a fraction of a wavelength means that, throughout breaking, the measured pressures at an impacted structure vary significantly even across globally similar waves (van Meerkerk et al 2020). Additionally, third-order wave-wave interactions at a fluid-structure interface can increase wave run-up height by twice that expected by linear wave theory (Zhao et al 2017) and the run-up of long waves can be amplified up to 12 times through nonlinear dispersion, reflection, interference and abrupt changes in bathymetry (Herterich & Dias 2019;Viotti, Carbone & Dias 2014). Abrupt changes in bathymetry that can be expected close to the coast can also trigger the formation of extreme waves through the interaction between first-order waves and their second-order bound harmonics (Li et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to waves that shoal gradually across smooth bathymetry, and run up gentle slopes-which are well-described and amenable to mathematical modelling-waves at rocky coasts are far less studied. They are difficult to measure, and equally difficult to model (Dodet et al, 2018;Herterich and Dias, 2019). Thus, there are few data for storm-wave runup in those environments.…”
Section: Introductionmentioning
confidence: 99%